Review of protocols used in Multicasting Communication (International Journal of Engineering and Computer Science, 2017)
In the age of multimedia and high speed network. Multicast is one of the mechanism by which the power of the internet can be further harnessed in an efficient manner. Multicast services have been increasingly used by various continues media application. Multicasting is the ability of communication network to accept a single message from an application and deliver copies of the message to multiple recipients of different location. This paper provides the role of protocols in multicast communication.